The effect of the Original MethOd at pharmacy To ENhAnce Support for Health Improvement in the limited Japanese proficiency patients visiting local community pharmacy: A randomized controlled trial. Issue 2 (February 2022) - Suzuki, Shota; Kato, Eri Toda; Sato, Keiko; Konda, Manako; Kuwabara, Yoshihiro; Yasuno, Shinji; Liu, Jinliang; Masuda, Izuru; Ueshima, Kenji
Highlights: Globalization creating linguistic and sociological problems worldwide for non-native patients visiting pharmacies. The current study aims to analyze the effect of adding our original method (OMOTENASHI) to the conventional method. OMOTENASHI consists of tools written in multiple languages and illustrations to clarify the effects and side effects. The overall comprehension level improved significantly by using our OMOTENASHI method, particularly from safety view. The study highlighted the importance of a tailor-made approach to pursue better patient care and health management. Abstract: Objectives: With an increase in globalization, the number of non-native-speaking citizens and tourists visiting local pharmacies is rapidly growing worldwide, creating linguistic and sociological problems. The aim of this study is to compare the effect of adding our original method, Original MethOd at pharmacy To ENhAnce Support for Health Improvement (OMOTENASHI), to the conventional medication counselling method (CMC) when counselling non-Japanese patients at the pharmacy. Methods: The OMOTENASHI consists of tools written in multiple languages and illustrations to clarify the effects and side effects, and to confirm patients' understanding. 71 non-Japanese patients were recruited and randomly assigned to the OMOTENASHI or to the CMC in a 1:1 ratio. Comprehension and satisfaction level were evaluated. Results: The overall comprehension level was significantly higher in the OMOTENASHI than in the CMC (75% vs 38%, p = 0.002), with a prominent difference in the recognition of the name, effects, side effects, precautions, and how to deal with side effects of the prescribed medication. Conclusion: The OMOTENASHI to be a helpful tool in providing essential information to non-native-speaking patients. Practice implication: The study highlighted the need to ensure every patient's safety and interests, and to avoid disadvantages caused by limited language proficiency in the globalization era.